Ranibizumab interacts with the VEGF-A/VEGFR-2 signaling pathway in human RPE cells at different levels. (July 2016) - Ranjbar, Mahdy; Brinkmann, Max Philipp; Tura, Aysegül; Rudolf, Martin; Miura, Yoko; Grisanti, Salvatore
Highlights: Ranibizumab is taken up into RPE cells and accumulates within the cells. VEGFR-2 is involved in the uptake mechanism of ranibizumab. Ranibizumab affects VEGF-A metabolism through extra- and intracellular pathways. Oxidative stress inhibits RPE cell proliferation. Ranibizumab enhances the anti-proliferative effect of oxidative stress. Abstract: Vascular endothelial growth factor (VEGF) secreted by the retinal pigment epithelium (RPE) plays an important role in ocular homeostasis, but also in diseases, most notably age-related macular degeneration (AMD). To date, anti-VEGF drugs like ranibizumab have been shown to be most effective in treating these pathologic conditions. However, clinical trials suggest that the RPE could degenerate and perish through anti-VEGF treatment. Herein, we evaluated possible pathways and outcomes of the interaction between ranibizumab and human RPE cells (ARPE-19). Results indicate that ranibizumab affects the VEGF-A metabolism in RPE cells from an extra- as well as intracellular site. The drug is taken up into the cells, with the VEGF receptor 2 (VEGFR-2) being involved, and decreases VEGF-A protein levels within the cells as well as extracellularly. Oxidative stress plays a key role in various inflammatory disorders of the eye. Our results suggest that oxidative stress inhibits RPE cell proliferation. This anti-proliferative effect on RPE cells is significantly enhanced through ranibizumab, which does not inhibit RPE cell proliferation substantially in absence of relevant oxidative stress. Therefore, we emphasize that anti-VEGF treatment should be selected carefully in AMD patients with preexistent extensive RPE atrophy.